Studi Deskriptif Fungsi Pengajar sebagai Penyemangat Pada Mata Pelajaran IPS di Kelas 05 SDN 045 Wilayah Kota Bengkulu - Yasi Korniati; Sri Dadi; Nani Yuliantini (Universitas Bengkulu, 2019)
The purpose of this assignment is to be able to describe the function of the instructor as an encouragement during social studies in class 05 of SDN 045 in the city of Bengkulu. The type of research used in this study is qualitative. Research subjects are teachers and students of 05 SDN 045 Kota Bengkulu. The research instrument is self-researcher by using observation guideline, interview guide. Data collection techniques used observation, and interviews. The Data that has been obtained is analyzed through data reduction, data presentation and conclusion drawing.Validity of data using extension of observation, increasing persistence, triangulation of data, triangulation of source, triangulation technique, triangulation time. The result of the research shows that as a motivator in IPS learning, the teacher has (1) clarified the purpose of achievement, (2) Increased the student's interest, (3) Creating a fun atmosphere in learning, (4) Giving reasonable praise to every student's happiness, (5) Evaluate, (6) Comment on students' work results, (7) Create competition and cooperation. from the final results of the study concluded that the role of teachers as a motivator in IPS learning there are some that have been implemented and some have not been implemented, but in the use of learning methods and utilization of instructional media so that learning activities can be implemented more optimal.The purpose of this assignment is to be able to describe the function of the instructor as an encouragement during social studies in class 05 of SDN 045 in the city of Bengkulu. The type of research used in this study is qualitative. Research subjects are teachers and students of 05 SDN 045 Kota Bengkulu. The research instrument is self-researcher by using observation guideline, interview guide. Data collection techniques used observation, and interviews. The Data that has been obtained is analyzed through data reduction, data presentation and conclusion drawing.Validity of data using extension of observation, increasing persistence, triangulation of data, triangulation of source, triangulation technique, triangulation time. The result of the research shows that as a motivator in IPS learning, the teacher has (1) clarified the purpose of achievement, (2) Increased the student's interest, (3) Creating a fun atmosphere in learning, (4) Giving reasonable praise to every student's happiness, (5) Evaluate, (6) Comment on students' work results, (7) Create competition and cooperation. from the final results of the study concluded that the role of teachers as a motivator in IPS learning there are some that have been implemented and some have not been implemented, but in the use of learning methods and utilization of instructional media so that learning activities can be implemented more optimal.